Exploratory study on sequestration of some essential metals by indigo carmine food dye - Zanoni, Thalita Boldrin [UNESP]; Cardoso, Arnaldo Alves [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP]; Ferreira, Antonio Aparecido Pupim [UNESP] (FapUNIFESP (SciELO), 2010)
Indigo carmine forms a stable complex with different ions, and the stability constant of the complexes were evaluated as log K equal to 5.75; 5.00; 4.89 and 3.89 for complexes with Cu(II), Ni(II), Co(II) and Zn(II) ions, respectively, in 0.1 mol L -1 carbonate buffer solution at pH 10. The interaction between Cu(II) ions and indigo carmine (IC) in alkaline medium resulted in the formation of the Cu 2(IC) complex, measured by the spectrophotometric method, with a stoichiometric ratio between indigo carmine and metal ions of 2:1 (metal-ligand). The reported method has also been successfully tested for determination of copper in pharmaceutical compounds based on copper-gluconate without pre-treatment.
Keywords: Copper/determination; Food dye/complexation; Indigo carmine; Metal sequestration; Spectrophotometric analysis; buffer; carbonic acid; cobalt; copper ion; food dye; gluconate copper; indigo carmine; nickel; zinc ion; alkalinity; chemical analysis; chemical interaction; chemical structure; complex formation; pH; spectrophotometry; stoichiometry